(untitled) (Perioperaciina Medicina, 2023)
This publication discusses the problems of treatment of severe intra-abdominal infections, namely empirical antimicrobial therapy for secondary peritonitis in view of the current state of the issue as understood by the authors, as well as modern guidelines and orders of the Ministry of Health of Ukraine. The use of well-known, but new for Ukraine drug, such as piperacillin / tazobactam, carbapenems, reserve antibiotics, is explored. We do not consider candidal, primary and tertiary peritonitis here, we hope to pay attention to this in future publications.